The Principle and Application of Achromatic Metalens - Runsheng Liu; Lihua Li; Jian Zhou (Micromachines)
Metalenses, as ultrathin planar optical devices based on metasurfaces, have attracted significant research interest in recent years due to their compact structure and versatile light manipulation, showing great potential to replace traditional lenses in specific applications. This review focuses on the fundamental principles of geometric and propagation phases of metalenses, introducing their applications in achromatic aberration correction, and emphasizing their advantages and limitations. We further discuss the application of multilayer metalenses in zoom optical systems and summarize methods such as topology optimization and inverse design to enhance the efficiency of metalenses. Special attention is given to comparing broadband and discrete achromatic correction, highlighting their respective working principles, design challenges, and practical implications. Additionally, recent advances in using deep learning for image-side aberration correction are briefly discussed. Finally, we highlight various practical applications of metalenses and discuss future research directions.